An Art Auction as a Perspective form of Activity at the Regional Art Production Market in Russia - CHERNYAEVA, Irina Valeryevna; STEPANSKAYA, Yelina Vyacheslavovna; SINO, Guan (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
The article covers on the form of art market activity – selling art works via auctions; historical stages of auction development and auction types are presented. Art auction as a trade mechanism is the most effective for selling art works, because it can define current market value of an artwork and form quotations and rating of an artist. Enormous information resources and virtual space’s great business potential provide substantial opportunities to distribute auctions in Russian regions. The end of the XX century for the world art market was a kind of revolution due to the active Internet reclaiming by the largest auction houses. Authors analyzed new forms of trading: online auctions and e-commerce, which development has been intensive at the turn of the XX-XXI centuries in the central part of Russia. These forms should be implemented in the region art life.